Validity and reliability of MOS short form health survey (SF-36) for use in India - Richa Sinha; Wim J A van den Heuvel; Perianayagam Arokiasamy (Wolters Kluwer Medknow Publications, 2013)
Background: Health is defined as the state of complete physical, mental and social well-being than just the absence of disease or infirmity. In order to measure health in the community, a reliable and validated instrument is required. Objectives: To adapt and translate the Medical Outcomes Study Short-Form Health Survey (SF-36) for use in India, to study its validity and reliability and to explore its higher order factor structure. Materials and Methods: Face-to-face interviews were conducted in 184 adult subjects by two trained interviewers. Statistical analyses for establishing item-level validity, scale-level validity and reliability and tests of known group comparison were performed. The higher order factor structure was investigated using principal component analysis with varimax rotation. Results: The questionnaire was well understood by the respondents. Item-level validity was established using tests of item internal consistency, equality of item-scale correlations and item-discriminant validity. Tests of scale-level validity and reliability performed well as all the scales met the required internal consistency criteria. Tests of known group comparison discriminated well across groups differing in socio-demographic and clinical variables. The higher order factor structure was found to comprise of two factors, with factor loadings being similar to those observed in other Asian countries. Conclusion: The item-and scale-level statistical analyses supported the validity and reliability of SF-36 for use in India.